Proliferative activity of antigen-specific CD154+ T cells against bacterial and fungal respiratory pathogens in cystic fibrosis decreases after initiation of highly effective CFTR modulator therapy - Eschenhagen, Patience N.; Bacher, Petra; Grehn, Claudia; Mainz, Jochen G.; Scheffold, Alexander; Schwarz, Carsten (Frontiers in Pharmacology, 2023)
Background: Together with impaired mucociliary clearance, lung disease in cystic fibrosis (CF) is driven by dysregulation of innate and adaptive immunity caused by dysfunctional CFTR (Cystic Fibrosis Transmembrane Conductance Regulator), leading to airway infection and hyperinflamma-tion. The highly effective CFTR modulator therapy (HEMT) elexacaftor/tezacaftor/ivacaftor (ETI) generates substantial improvements in clinical outcomes of people with CF (pwCF) by restoration of CFTR activity. Aberrant immune responses of lymphocytes due to CFTR dysfunction has been described in the past, but not the effects of CFTR restoration by HEMT on these cells. We aimed to examine the effect of ETI on the proliferation activity of antigen-specific CD154(+) T cells against bacterial and fungal species relevant in CF and on total IgG and IgE as markers of B cell adaptive immunity. Methods: We performed ex vivo analyses of Ki-67 expression in antigen-specific CD154(+) T cells against Pseudomonas aeruginosa, Staphylococcus aureus, Aspergillus fumigatus, Scedosporium apiospermum and Candida albicans from 21 pwCF by cytometric assay based on antigen-reactive T cell enrichment (ARTE), and analysis of total serum IgE an IgG before and after initiation of ETI. Results: Mean Ki-67 expression in antigen-specific CD154(+) T cells against Pseudomonas aeruginosa, Aspergillus fumigatus, Scedosporium apiospermum and Candida albicans, but not Staphylococcus aureus, mean total serum IgG and mean total serum IgE decreased significantly after initiation of ETI. No correlation was found to change in sputum microbiology of the examined pathogens. Mean BMI and FEV1 increased significantly. Conclusions: HEMT is associated with decreased antigen-specific CD154(+) T cell proliferation activity in our cohort, independent of findings in sputum microbiology of the examined pathogens. Together with the observed clinical improvement and the decrease in total IgE and IgG, this indicates effects due to CFTR restoration on CD154(+) T cells by ETI and a reduction of B cell activation and subsequent lower immunoglobulin synthesis with HEMT therapy. These results confirm earlier evidence of CFTR dysfunction in T and B cells leading directly to aberrant immune responses with hyperinflammation.